2012
DOI: 10.2176/nmc.52.482
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Intrathecal Baclofen Therapy in Japan

Abstract: Intrathecal baclofen (ITB) therapy was approved for health insurance coverage in 2005 for the treatment of patients whose spasticity could not be adequately controlled by conventional therapy, and is currently being used to treat around 300 patients nationwide in Japan. Various reports have examined the efficacy and safety of ITB therapy, but no report has evaluated the patient quality of life and medical costs in Japan. A cost-utility analysis of ITB was conducted by time period in six severely spastic patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Hattori et al. examined direct and indirect costs of six spastic adult patients in Japan for 1 year before and after implant . This study reported increased direct medical costs and decreased indirect and total costs.…”
Section: Discussionmentioning
confidence: 99%
“…Hattori et al. examined direct and indirect costs of six spastic adult patients in Japan for 1 year before and after implant . This study reported increased direct medical costs and decreased indirect and total costs.…”
Section: Discussionmentioning
confidence: 99%
“…We identified only three studies that obtained utilities empirically from patients or their caregivers [13,16,27] and two more that derived them indirectly [2,14]. In the first group, the average utility gains ranged from 0.10 to 0.42, whereas in the studies that derived them in an indirect way, the average gain ranged from 0.27 to 0.50.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, recent work based on actuarial projections informed by retrospective analysis of commercial administrative claims data in the United States suggests that compared to conventional treatment, the costs of ITB Therapy are largely off-set by savings in the consumption of other health-care resources when the entire lifetime of patients is considered [12]. Existing cost-effectiveness analyses of ITB Therapy also point into this direction, but these studies either only focused on pediatric patients [13,14], used nonempirical data [2,14], did not express the result in terms of quality-adjusted life-years (QALYs) gained [15], and/or had a relatively short-time horizon [2,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Çalışma sonunda FBÖ motor fonksiyonları ağırlıklı olarak anlamlı düzeyde artmıştır. Literatürü incelediğimizde yapılan çalışmalarla uyumlu bulunmuştur (17,21 Bu çalışmada fiyat-maliyet incelemesi yapılmamış, ancak literatürde İTB konvansiyonel spastisite tedavileriyle karşılaştırıldığı zaman maliyet etkin olduğu değerlendirilmiştir (30,31).…”
Section: Discussionunclassified